Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/2017pa003087
|View full text |Cite
|
Sign up to set email alerts
|

New northwest Pacific radiolarian data as a tool to estimate past sea surface and intermediate water temperatures

Abstract: A new radiolarian data set for transfer function estimates of past sea surface temperature (SST) and intermediate water temperature was developed in this study for the northwestern Pacific Ocean covering a region from 1° to 50°N and 120° to 167°E. We analyzed 87 sediments surface samples, selected 30 species and/or species group found in shallow water for estimating past summer SST and 17 species and/or species group found in the intermediate water for estimating past intermediate water temperature. Since the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
84
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(86 citation statements)
references
References 78 publications
2
84
0
Order By: Relevance
“…Young forms of Spongodiscidae, whose taxonomy is still unsettled, are often named as Spongodiscus resurgens Ehrenberg group (e.g., Itaki 2009;Matsuzaki et al 2015a). However, whichever name is used, this form is likely related to the shallow subsurface waters of transitional subarctic areas in the Northwest Pacific (e.g., Kamikuri et al 2008;Matsuzaki and Itaki 2017;Okazaki et al 2004). In our study, both the species and species group were found at Site U1425 throughout the period since 9.5 Ma.…”
Section: Relative Abundance Of Abundant Speciesmentioning
confidence: 59%
See 4 more Smart Citations
“…Young forms of Spongodiscidae, whose taxonomy is still unsettled, are often named as Spongodiscus resurgens Ehrenberg group (e.g., Itaki 2009;Matsuzaki et al 2015a). However, whichever name is used, this form is likely related to the shallow subsurface waters of transitional subarctic areas in the Northwest Pacific (e.g., Kamikuri et al 2008;Matsuzaki and Itaki 2017;Okazaki et al 2004). In our study, both the species and species group were found at Site U1425 throughout the period since 9.5 Ma.…”
Section: Relative Abundance Of Abundant Speciesmentioning
confidence: 59%
“…Species such as L. setosa, Spongodiscidae juvenile, and P. gracilipes are well-known extant species related to subarctic areas. Based on previous studies, we know that L. setosa is related to the shallow water of subarctic to arctic areas of the Northern Hemisphere (Atlantic and Pacific oceans) (Boltovskoy and Correa 2016;Matsuzaki and Itaki 2017;Okazaki et al 2004). At Site U1425, this species was recorded between 3.69 and 0 Ma, and its mean relative abundance is 1.7% (SD = 3.3; N = 44) ( Fig.…”
Section: Relative Abundance Of Abundant Speciesmentioning
confidence: 87%
See 3 more Smart Citations